1991
DOI: 10.1002/hrm.3930300102
|View full text |Cite
|
Sign up to set email alerts
|

The managerial implications of changing work force demographics: A scoping study

Abstract: The demographic changes currently underway in the United States have been widely anticipated and discussed by scholars and practitioners, but little is known about what impacts, if any, have already been experienced by employers. This article reports on a field study that asked managers in large US corporations to describe how and to what extent demographic changes have affected their businesses. Changing work force demographics were interpreted by managers as having two distinct components: a reduction in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 3 publications
0
13
1
Order By: Relevance
“…The literature has indicated that the increase in the shortage of skilled labor, the increasing number of migrant employees, the increasing competitive environment, and the rapid rate of change puts an organization under pressure to adapt to these changes, through effective training programs and courses to empower its diverse workforce (Jackson et al, 1992;Loveman and Gabarro, 1991). In spite of the growing importance of training, the findings of this study indicated that training practices for diverse employees are not adequate (mean ϭ 4.22).…”
Section: Training and Development Issuescontrasting
confidence: 48%
See 2 more Smart Citations
“…The literature has indicated that the increase in the shortage of skilled labor, the increasing number of migrant employees, the increasing competitive environment, and the rapid rate of change puts an organization under pressure to adapt to these changes, through effective training programs and courses to empower its diverse workforce (Jackson et al, 1992;Loveman and Gabarro, 1991). In spite of the growing importance of training, the findings of this study indicated that training practices for diverse employees are not adequate (mean ϭ 4.22).…”
Section: Training and Development Issuescontrasting
confidence: 48%
“…The main problems that affect culturally diverse employees are inequality of income and bonuses, job recognition, promotion, and assignment of responsibilities (Grace, 1994;Jackson et al, 1992). Researchers have indicated that a lack of, or differences in, career planning, and organizational discrimination may be responsible for the loss of promotional opportunities that would better prepare nontraditional managers for senior-level positions (Kogod, 1992;Loveman and Gabarro, 1991;Schreiber et al, 1993).…”
Section: Remunerationmentioning
confidence: 96%
See 1 more Smart Citation
“…According to Richard and Kirby (1999), human resource practices regarding career advancement must reflect diversity issues in order to overcome negative perceptions from diverse employees. Thus, such failure in providing a career development plan for diverse employees would negatively affect their motivation, morale, creativity, innovation and performance (Loveman & Gabarro, 1991;Morrison, 1992;Ragins & Scandura, 1994).…”
Section: Career Advancement Diversity Management Practicesmentioning
confidence: 99%
“…Research in the United Kingdom indicates that, where older workers are being recruited into the labor force, it tends to be predominantly into part-time, low skill, low pay, low responsibility, and repetitive jobs (27). Lack of appropriate skills is often cited as being a major factor in discouraging the recruitment of older workers (14,28). Some researchers have pointed out that, although discrimination against older workers operates across all socioeconomic groups, its greatest impact is on lower skilled groups (24).…”
Section: Employment Implications Of Attitudes Towards Older Workersmentioning
confidence: 99%